Arabic humanities, Islamic thought : essays in honor of Everett K. Rowson - Rowson, Everett K.; Lowry, Joseph E.; Toorawa, Shawkat M. (Islamic History and Civilization, 2017)
This volume brings together studies that explore the richness of the Arabic literary tradition and of Islamic intellectual life, from the beginnings of Islam to the present. The contributors cover an unusually wide range of subjects, including such topics as guile in the Quran, marriage in Islamic law, early esoterica, commentaries on al-Ḥarīrī's Maqamāt , Hellenistic philosophy in Arabic, medieval music and song, scurrilous poetry, Arabic rhetoric, cursing, the modern social and legal history of the Middle East, al-Kharrat's modernist project, and contemporary Islamic thought and responses to it. The volume's range reflects the enormous breadth of Everett Rowson's scholarship and his impact over a lifetime of publishing, editing, teaching, and mentoring in the many fields that constitute the Arabic humanities and Islamic thought. Contributors: Ali Humayun Akhtar, Thomas Bauer, Hans Hinrich Biesterfeldt, Kevin van Bladel, Marilyn Booth, Michael Cooperson, Kenneth M. Cuno, Geert Jan van Gelder, Hala Halim, Lara Harb, David Hollenberg, Matthew L. Keegan, David Larsen, Joseph E. Lowry, Zainab Mahmood, Jon McGinnis, Jeannie Miller, John Nawas, Bilal Orfali, Alex Popovkin, Dwight F. Reynolds, Susan A. Spectorsky, Tara Stephan, Adam Talib, Sarra Tlili, Shawkat M. Toorawa, James Toth, Mark S. Wagner.